Key aspects affecting the performances of high-K dielectrics based single-gate and dual-gate OTFTs. (2022) - Gupta, Srishti; Kumar Singh, Manish
Abstract: The single-gate (SG) and dual-gate (DG) organic thin-film transistors (OTFTs) performances have been analyzed by using high dielectric constant material. The dielectric and gate electrode material variation does the comparative study on SG (bottom-gate bottom-contact configuration) and DG-based OTFTs. Variation in thickness of the dielectric layer (step size 2) and channel length (step size 10) results in a deviation in the performance parameters like threshold voltage, mobility, ION /IOFF current ratio, subthreshold swing, trans-conductance, etc. Such variations in the performance of OTFT have been observed by using 2D numerical devices ATLAS simulator. Subsequently, it is analyzed that reduction in channel length from 50 µm to 10 µm leads to an increase in the drain current from −9.88 × 10 −10 A to −5.8 × 10 −9 A (in case of DG-OTFT) and from −9.84 × 10 −11 A to −5.3 × 10 −9 A (in case of SG-OTFT). Similarly, the reduction in dielectric layer thickness from 10 nm to 2 nm leads to an increase in the drive current/the current ratio from 3.9 × 10 12 to 1.3 × 10 13 (in case of SG-OTFT) and from 1.8 × 10 5 to 1.5 × 10 6 (in case of DG-OTFT). So achieving a better result, we switch to DG- OTFT compared to SG-OTFT, which would be helpful in various future applications like chemical sensors, circuits, RFIDs, etc.